The Irish writer and the world - Kiberd, Declan (Cambridge University Press, 2005)
Declan Kiberd here synthesises the themes that have occupied him throughout his career as a leading critic of Irish literature and culture. This book demonstrates afresh the extraordinary range, astuteness and wit that have made him a defining voice in Irish studies and beyond.